Efficient Single-Gene and Gene Family Editing in the Apicomplexan Parasite Eimeria tenella Using CRISPR-Cas9 - Hu, Dandan; Tang, Xinming; Ben Mamoun, Choukri; Wang, Chaoyue; Wang, Si; Gu, Xiaolong; Duan, Chunhui; Zhang, Sixin; Suo, Jinxia; Deng, Miner; Yu, Yonglan; Suo, Xun; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Eimeria species are pathogenic protozoa with a wide range of hosts and the cause of poultry and livestock coccidiosis, a disease recognized as a major risk to global food security. These parasites encode a genome of ~8000 genes that control a highly coordinated life cycle of asexual replication and sexual differentiation, transmission and virulence. However, the function and physiological importance of the large majority of these genes remain unknown mostly due to the lack of tools for systematic analysis of gene functions. Here, we report the first application of CRISPR-Cas9 gene editing technology in E. tenella for analysis of gene function at a single gene level as well as for systematic functional analysis of an entire gene family. Using a transgenic line constitutively expressing Cas9, we demonstrated successful and efficient loss of function through non-homologous end joining as well as guided homologous recombination. Application of this approach to the study of the localization of EtGRA9 revealed that the gene encodes a secreted protein whose cellular distribution varied during the life cycle. Systematic disruption of the ApiAp2 transcription factor gene family using this approach revealed that 23 of the 33 factors expressed by this parasite are essential for development and survival in the host. Our data thus establish CRISPR-Cas9 as a powerful technology for gene editing in Eimeria and will set the stage for systematic functional analysis of its genome to understand its biology and pathogenesis, and will make it possible to identify and validate new targets for coccidiosis therapy.